High-efficiency battery assembly and preparation method thereof
By using a composite preparation method of modified flame retardant materials and SiC reinforced materials, the flame retardant performance and strength of the battery module are improved, and the thermal runaway and service life problems that may occur in the battery module under high energy density are solved, achieving further development High safety and durability.
Patent Information
- Application Number
- CN202411388592.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-10
AI Technical Summary
Battery components may cause overheating, short circuit or physical damage under high energy density operating conditions, leading to thermal runaway, and insufficient flame retardant performance may cause fire or explosion, and insufficient strength may lead to shortening of service life.
The composite preparation method of melamine-modified flame retardant material, SiC-enhanced flame retardant material and polyphosphate flame retardant material is adopted. The composite flame retardant material is formed by slowly dropping the addition of ethylenediamine and pyridine to carry out reflux reaction, and the composite flame retardant material is formed, and it is combined with silicone resin and 2. Silicon oxide fillers, dispersants and coupling agents are mixed to prepare coatings, coat back panels and lay photovoltaic modules to improve flame retardant performance and strength.
It significantly improves the flame retardant performance and strength of photovoltaic modules, reduces the risk of fire and explosion, extends service life, and reduces component costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaics, and in particular to a high-efficiency battery assembly and a preparation method thereof. Background Art
[0002] With the growth of global demand for clean energy and the popularity of electric vehicles, the role of battery components has become increasingly prominent, and its modern value is reflected in the following aspects: First, battery components play a vital role in the storage and utilization of renewable energy. Renewable energy such as wind and solar energy is volatile, so battery components can store excess electricity for use during peak demand periods. This energy storage capacity not only improves energy utilization efficiency, but also reduces dependence on fossil fuels and promotes the transformation of green energy. The advancement of modern battery technology has made large-scale energy storage systems more economical and feasible, promoting the optimization of energy structure and environmental protection. Second, battery components play a key role in emergency power supply and backup power systems. Whether it is a home backup power supply or a backup battery system for a large data center, they can provide continuous power support during power outages to ensure the normal operation of key equipment and systems. This application is particularly important in natural disasters and emergencies, enhancing society's emergency response capabilities and the resilience of infrastructure.
[0003] However, under high energy density operating conditions, battery components may cause problems such as overheating, short circuit or physical damage, all of which may lead to thermal runaway of the battery. If the flame retardant performance of the battery component is insufficient, once a short circuit or other failure occurs, it may cause a fire or explosion, causing serious harm to users and the environment. Therefore, it is necessary to improve the flame retardant performance of the battery, so as to effectively reduce the risk of fire and explosion and ensure the safety of the battery in various application scenarios. In addition, the battery is susceptible to external shocks, vibrations and other physical stresses during use, which may cause damage to the internal structure. If the strength of the battery component is insufficient, these external shocks will cause internal short circuits or leakage in the battery, thereby shortening the battery life.
[0004] In order to overcome the defects of the prior art, the present invention provides a high-efficiency battery assembly and a preparation method thereof. Summary of the invention
[0005] The object of the present invention is to provide a high-efficiency battery assembly and a preparation method thereof to solve the problems in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a high-efficiency battery assembly comprises the following steps: Step 1: Mix melamine modified flame retardant material, SiC reinforced flame retardant material, polyphosphoric acid flame retardant material and 1,4-dioxane, then slowly add ethylenediamine and pyridine, reflux at 90-100°C for 3-5h, filter, wash with water, wash with alcohol, and dry after the reaction to obtain a composite flame retardant material; mix silicone resin, silica filler, composite flame retardant material, dispersant, and coupling agent, stir and ball mill thoroughly to obtain a coating; Step 2: Clean the backplane with ethanol, rinse with deionized water, apply paint, and cure at 100-180℃ for 1-2h to obtain a pretreated backplane; then lay glass, ethylene-vinyl acetate copolymer, main grid-free rectangular battery cell, copper welding wire composite film, POE, and pretreated backplane in sequence, seal the edges after laying, and then laminate, frame, wire, and package to prepare a photovoltaic module.
[0007] More optimally, in step one, the preparation process of the melamine modified flame retardant material is: mixing melamine and deionized water, heating the oil bath to 100-110°C, then dropping phytic acid and γ-aminopropyltriethoxysilane, and continuing the reaction for 5-7h to obtain a modified flame retardant liquid; then mixing the modified flame retardant liquid, cyanuric chloride and acid binding agent triethylamine, stirring and reacting at 15-20°C for 4-5h to obtain a melamine modified flame retardant material.
[0008] More optimally, the reaction molar ratio of phytic acid, melamine and γ-aminopropyltriethoxysilane is 1:(4-5):1; the reaction mass ratio of modified flame retardant liquid, cyanuric chloride and acid binding agent triethylamine is (3-4):2:1.
[0009] More optimally, in step one, the preparation process of the SiC reinforced flame retardant material is: deionized water, anhydrous ethanol and γ-aminopropyltriethoxysilane are mixed, ultrasonically dispersed for 15-20 minutes, and then SiC whiskers are added, stirred and reacted at 45-50°C for 30-40 minutes to obtain a modified SiC solution; then the modified SiC solution, cyanuric chloride and acid binding agent triethylamine are mixed, stirred and reacted at 15-20°C for 4-5 hours to obtain a SiC reinforced flame retardant material.
[0010] More optimally, the contents of the components of the SiC reinforced flame retardant material are: by mass, 100-120 parts of deionized water, 200-220 parts of anhydrous ethanol, 2-3 parts of γ-aminopropyltriethoxysilane, 2-3 parts of SiC whiskers, 1.8-2.0 parts of cyanuric chloride, and 1-2 parts of acid binding agent triethylamine.
[0011] More optimally, in step one, the preparation process of the polyphosphoric acid flame retardant material is: hexachlorotriphosphazene, 4-hydroxyphenyl phosphate and acetonitrile are mixed, stirred at 75-80°C for 3-5h, and then pyridine is added to continue the reaction for 6-8h to obtain the polyphosphoric acid flame retardant material.
[0012] More optimally, the contents of the components of the polyphosphoric acid flame retardant material are: by mass, 17-20 parts of hexachlorotripolyphosphazene, 34-40 parts of 4-hydroxyphenyl phosphate, 200-250 parts of acetonitrile, and 16-20 parts of pyridine.
[0013] More optimally, in step one, the contents of each component of the composite flame retardant material are: by mass, 180-200 parts of melamine modified flame retardant material, 310-320 parts of SiC reinforced flame retardant material, 270-280 parts of polyphosphoric acid flame retardant material, 150-350 parts of 1,4-dioxane, 4.8-5.2 parts of ethylenediamine, and 9.8-10.2 parts of pyridine.
[0014] More optimally, in step one, the contents of the various components of the coating are: by mass fraction, 15-20% silica filler, 10-15% composite flame retardant material, 0.5-1.5% dispersant, 0.5-1.5% coupling agent, and the remainder is silicone resin; the dispersant is oleamide; and the coupling agent is diethyl titanate.
[0015] More optimally, in step 2, the backplane is divided into side A and side B, side A is the side in contact with the outside, side B is the side connected to various photovoltaic modules, and the paint is applied to side A; lamination process parameters: lamination temperature is 130-140°C, and lamination time is 10-14min.
[0016] Beneficial effects of the present invention: The present invention is characterized in that, in step 1, a modified flame retardant liquid is prepared by adding melamine, phytic acid and γ-aminopropyltriethoxysilane; and then the modified flame retardant liquid, cyanuric chloride and acid-binding agent triethylamine are mixed, and a melamine modified flame retardant material is obtained by stirring and reacting. In this step, melamine and γ-aminopropyltriethoxysilane can react with the phosphoric acid group in phytic acid to form an effective flame retardant cross-linked network; in addition, since the reaction molar ratio of phytic acid, melamine and γ-aminopropyltriethoxysilane is controlled to be 1: (4-5): 1 in this step, a certain amount of amino groups remain in the modified flame retardant liquid generated in this step, and the remaining amino groups can be mixed with cyanuric chloride and acid-binding agent triethylamine in the next step to undergo a substitution reaction, thereby obtaining a melamine modified flame retardant material.
[0017] In step 1, a modified SiC solution is prepared by adding γ-aminopropyltriethoxysilane, SiC whiskers and solvent; the modified SiC solution, cyanuric chloride and acid-binding agent triethylamine are mixed, and the SiC reinforced flame retardant material is obtained by stirring and reacting. In this step, SiC whiskers with good reinforcement performance are modified with γ-aminopropyltriethoxysilane to obtain a modified SiC solution with active amino groups. The modified SiC solution cyanuric chloride and acid-binding agent triethylamine are then mixed, and a substitution reaction occurs to obtain a SiC reinforced flame retardant material.
[0018] In step one, a polyphosphoric acid flame retardant material is prepared by adding hexachlorotriphosphazene, 4-hydroxyphenyl phosphate, acetonitrile and pyridine. Melamine-modified flame retardant material, SiC-reinforced flame retardant material, polyphosphoric acid flame retardant material, 1,4-dioxane, ethylenediamine and pyridine are subjected to reflux reaction to obtain a composite flame retardant material. In this step, hexachlorotriphosphazene and 4-hydroxyphenyl phosphate undergo a nucleophilic substitution reaction under the catalytic action of pyridine to obtain a polyphosphoric acid flame retardant material. Then, melamine-modified flame retardant material, SiC-reinforced flame retardant material, polyphosphoric acid flame retardant material and ethylenediamine are mixed, and a composite flame retardant material is obtained by a substitution reaction.
[0019] Finally, the present invention uses silicone resin, silica filler, composite flame retardant material, dispersant and coupling agent as raw materials to prepare coating. The backplane is cleaned and coated with coating to obtain a pre-treated backplane, and then glass, ethylene-vinyl acetate copolymer, main grid-free rectangular battery cell, copper welding wire composite film, POE, and pre-treated backplane are laid in sequence. After laying, the photovoltaic module is prepared by edge sealing, lamination, framing, wiring, and packaging. The present invention uses main grid-free rectangular battery cells to reduce the blocking area on the battery cell on the one hand, greatly improving the power and conversion efficiency of the module; on the other hand, it can reduce the amount of silver paste used in the battery cell, thereby reducing the cost of the module. In addition, the composite flame retardant material can significantly improve the flame retardant properties of the backplane by forming a P-Si-N flame retardant cross-linked network, thereby improving the flame retardant properties of the photovoltaic module. In addition, since SiC whisker reinforcement material is also introduced into the material, the photovoltaic module prepared by the present invention can also effectively improve the strength and hardness. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Source of raw materials: SiC whiskers, provided by Qinhuangdao Yinuo High-tech Materials Development Co., Ltd., φ 5-10μm, L 50-100μm, analytical grade; silicone resin, provided by Huizhou Saikewei Industrial Co., Ltd., model 1-2577; silica filler, provided by Lingshou County Malin Mineral Products Processing Plant, particle size 10μm; glass, provided by Xinyi Company, specifically 3.2mm thick coated tempered embossed glass; ethylene-vinyl acetate copolymer, provided by Foster Company, model F406PS, 0.45mm thick; no main grid matrix Shaped battery cell, provided by Aixu Company, 182×210mm, 0BB battery cell; copper welding wire composite film, including copper welding wire and adhesive film, copper welding wire provided by Yubang Company, diameter 0.2mm, tinned copper welding wire; adhesive film provided by Foster Company, thickness 0.1mm, width 178mm, model CF15; POE, provided by Foster Company, 0.45mm thickness, model EP304; backplane, provided by Saiwu Company, thickness 0.3115mm, model KPf205A(R); in terms of mass parts, one portion is 1g.
[0022] Example 1: Step 1: 4 mol of melamine and deionized water were mixed, the oil bath was heated to 110°C, and then 1 mol of phytic acid and 1 mol of γ-aminopropyltriethoxysilane were added dropwise, and the reaction was continued for 7 hours to obtain a modified flame retardant liquid; then 3 g of the modified flame retardant liquid, 2 g of cyanuric chloride and 1 g of an acid binding agent triethylamine were mixed, and the mixture was stirred and reacted at 20°C for 5 hours to obtain a melamine-modified flame retardant material; 100 g of deionized water, 200 g of anhydrous ethanol and 2 g of γ-aminopropyltriethoxysilane were mixed, ultrasonically dispersed for 20 min, and then 2 g of SiC whiskers were added, stirred and reacted at 50° C. for 40 min to obtain a modified SiC solution; then the modified SiC solution, 1.8 g of cyanuric chloride and 1 g of acid-binding agent triethylamine were mixed, stirred and reacted at 20° C. for 5 h to obtain a SiC reinforced flame retardant material; 17 g of hexachlorotriphosphazene, 34 g of 4-hydroxyphenyl phosphate and 200 g of acetonitrile were mixed, stirred at 80° C. for 5 h, and then 16 g of pyridine was added to continue the reaction for 8 h to obtain a polyphosphoric acid flame retardant material; 180g of melamine modified flame retardant material, 310g of SiC reinforced flame retardant material, 270g of polyphosphoric acid flame retardant material and 300g of 1,4-dioxane were mixed, and then 5g of ethylenediamine and 10g of pyridine were slowly added, and refluxed at 100°C for 5h. After the reaction was completed, the composite flame retardant material was obtained by filtering, washing with water, washing with alcohol, and drying; 69% of silicone resin, 15% of silica filler, 15% of composite flame retardant material, 0.5% of oleic acid amide, and 0.5% of diethyl titanate were mixed by mass fraction, and the mixture was fully stirred and ball-milled to obtain a coating; Step 2: Clean the backplane with ethanol, rinse with deionized water, apply paint, and cure at 180°C for 2 hours to obtain a pretreated backplane; then lay glass, ethylene-vinyl acetate copolymer, main grid-free rectangular battery cell, copper welding wire composite film, POE, and pretreated backplane in order, seal the edges after laying, laminate at 140°C for 15 minutes, frame, wire, and package to prepare a photovoltaic module; the backplane is divided into side A and side B, side A is the side in contact with the outside, and side B is the side connected to various photovoltaic modules, and the paint is applied to side A when coating.
[0023] Example 2: Step 1: 4 mol of melamine and deionized water were mixed, the oil bath temperature was raised to 105°C, and then 1 mol of phytic acid and 1 mol of γ-aminopropyltriethoxysilane were added dropwise, and the reaction was continued for 6 hours to obtain a modified flame retardant liquid; then 3 g of the modified flame retardant liquid, 2 g of cyanuric chloride and 1 g of an acid binding agent triethylamine were mixed, and the mixture was stirred and reacted at 17°C for 4.5 hours to obtain a melamine modified flame retardant material; 100 g of deionized water, 200 g of anhydrous ethanol and 2 g of γ-aminopropyltriethoxysilane were mixed, ultrasonically dispersed for 17 min, and then 2 g of SiC whiskers were added, stirred and reacted at 47° C. for 35 min to obtain a modified SiC solution; then the modified SiC solution, 1.8 g of cyanuric chloride and 1 g of acid-binding agent triethylamine were mixed, stirred and reacted at 17° C. for 4.5 h to obtain a SiC reinforced flame retardant material; 17 g of hexachlorotripolyphosphazene, 34 g of 4-hydroxyphenyl phosphate and 200 g of acetonitrile were mixed, stirred at 77° C. for 4 h, and then 16 g of pyridine was added to continue the reaction for 7 h to obtain a polyphosphoric acid flame retardant material; 180g of melamine modified flame retardant material, 310g of SiC reinforced flame retardant material, 270g of polyphosphoric acid flame retardant material and 300g of 1,4-dioxane were mixed, and then 5g of ethylenediamine and 10g of pyridine were slowly added, and refluxed at 95°C for 4h. After the reaction, the composite flame retardant material was obtained by filtering, washing with water, washing with alcohol and drying; 69% of silicone resin, 15% of silica filler, 15% of composite flame retardant material, 0.5% of oleic acid amide and 0.5% of diethyl titanate were mixed by mass fraction, and the mixture was fully stirred and ball-milled to obtain a coating; Step 2: Clean the backplane with ethanol, rinse with deionized water, apply paint, and cure at 140°C for 1.5 hours to obtain a pretreated backplane; then lay glass, ethylene-vinyl acetate copolymer, main grid-free rectangular battery cell, copper welding wire composite film, POE, and pretreated backplane in order, seal the edges after laying, laminate at 135°C for 13 minutes, frame, wire, and package to prepare a photovoltaic module; the backplane is divided into side A and side B, side A is the side in contact with the outside, and side B is the side connected to various photovoltaic modules, and the paint is applied to side A when coating.
[0024] Example 3: Step 1: 4 mol of melamine and deionized water were mixed, the oil bath was heated to 100°C, and then 1 mol of phytic acid and 1 mol of γ-aminopropyltriethoxysilane were added dropwise, and the reaction was continued for 5 hours to obtain a modified flame retardant liquid; then 3 g of the modified flame retardant liquid, 2 g of cyanuric chloride and 1 g of an acid binding agent triethylamine were mixed, and the mixture was stirred and reacted at 15°C for 4 hours to obtain a melamine-modified flame retardant material; 100 g of deionized water, 200 g of anhydrous ethanol and 2 g of γ-aminopropyltriethoxysilane were mixed, ultrasonically dispersed for 15 min, and then 2 g of SiC whiskers were added, stirred and reacted at 45° C. for 30 min to obtain a modified SiC solution; then the modified SiC solution, 1.8 g of cyanuric chloride and 1 g of acid-binding agent triethylamine were mixed, stirred and reacted at 15° C. for 4 h to obtain a SiC reinforced flame retardant material; 17 g of hexachlorotripolyphosphazene, 34 g of 4-hydroxyphenyl phosphate and 200 g of acetonitrile were mixed, stirred at 75° C. for 3 h, and then 16 g of pyridine was added to continue the reaction for 6 h to obtain a polyphosphoric acid flame retardant material; 180g of melamine modified flame retardant material, 310g of SiC reinforced flame retardant material, 270g of polyphosphoric acid flame retardant material and 300g of 1,4-dioxane were mixed, and then 5g of ethylenediamine and 10g of pyridine were slowly added, and refluxed at 90°C for 3h. After the reaction, the composite flame retardant material was obtained by filtering, washing with water, washing with alcohol and drying; 69% of silicone resin, 15% of silica filler, 15% of composite flame retardant material, 0.5% of oleic acid amide and 0.5% of diethyl titanate were mixed by mass fraction, and the mixture was fully stirred and ball-milled to obtain a coating; Step 2: Clean the backplane with ethanol, rinse with deionized water, apply paint, and cure at 100°C for 1h to obtain a pretreated backplane; then lay glass, ethylene-vinyl acetate copolymer, main grid-free rectangular battery cell, copper welding wire composite film, POE, and pretreated backplane in sequence, seal the edges after laying, laminate at 130°C for 10min, frame, wire, and package to prepare a photovoltaic module; the backplane is divided into side A and side B, side A is the side in contact with the outside, and side B is the side connected to various photovoltaic modules, and the paint is applied to side A when coating.
[0025] Comparative Example 1: The preparation step of the SiC reinforced flame retardant material is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: 4 mol of melamine and deionized water are mixed, the oil bath is heated to 110°C, and then 1 mol of phytic acid and 1 mol of γ-aminopropyltriethoxysilane are added dropwise, and the reaction is continued for 7 hours to obtain a modified flame retardant liquid; then 3g of the modified flame retardant liquid, 2g of cyanuric chloride and 1g of an acid binding agent triethylamine are mixed, and the reaction is stirred at 20°C for 5 hours to obtain a melamine modified flame retardant material; 17 g of hexachlorotriphosphazene, 34 g of 4-hydroxyphenyl phosphate and 200 g of acetonitrile were mixed, stirred at 80° C. for 5 h, and then 16 g of pyridine was added to continue the reaction for 8 h to obtain a polyphosphoric acid flame retardant material; 180g of melamine modified flame retardant material, 270g of polyphosphoric acid flame retardant material and 300g of 1,4-dioxane were mixed, and then 5g of ethylenediamine and 10g of pyridine were slowly added dropwise, and refluxed at 100°C for 5h. After the reaction was completed, the composite flame retardant material was obtained by filtering, washing with water, washing with alcohol, and drying; 69% of silicone resin, 15% of silica filler, 15% of composite flame retardant material, 0.5% of oleic acid amide, and 0.5% of diethyl titanate were mixed by mass fraction, and the mixture was fully stirred and ball-milled to obtain a coating; Step 2: Clean the backplane with ethanol, rinse with deionized water, apply paint, and cure at 180°C for 2 hours to obtain a pretreated backplane; then lay glass, ethylene-vinyl acetate copolymer, main grid-free rectangular battery cell, copper welding wire composite film, POE, and pretreated backplane in order, seal the edges after laying, laminate at 140°C for 15 minutes, frame, wire, and package to prepare a photovoltaic module; the backplane is divided into side A and side B, side A is the side in contact with the outside, and side B is the side connected to various photovoltaic modules, and the paint is applied to side A when coating.
[0026] Comparative Example 2: The preparation steps of melamine-modified flame retardant material and polyphosphoric acid flame retardant material are removed, and the rest are the same as Example 1, and the specific steps are as follows: Step 1: 100g of deionized water, 200g of anhydrous ethanol and 2g of γ-aminopropyltriethoxysilane are mixed, ultrasonically dispersed for 20min, and then 2g of SiC whiskers are added, and stirred at 50°C for 40min to obtain a modified SiC solution; then the modified SiC solution, 1.8g of cyanuric chloride and 1g of acid binding agent triethylamine are mixed, and stirred at 20°C for 5h to obtain a SiC reinforced flame retardant material; 310g of SiC reinforced flame retardant material and 300g of 1,4-dioxane were mixed, and then 5g of ethylenediamine and 10g of pyridine were slowly added dropwise, and the mixture was refluxed at 100°C for 5h. After the reaction was completed, the mixture was filtered, washed with water, washed with alcohol, and dried to obtain a composite flame retardant material; 69% of silicone resin, 15% of silica filler, 15% of composite flame retardant material, 0.5% of oleic acid amide, and 0.5% of diethyl titanate were mixed by mass fraction, and the mixture was fully stirred and ball-milled to obtain a coating; Step 2: Clean the backplane with ethanol, rinse with deionized water, apply paint, and cure at 180°C for 2 hours to obtain a pretreated backplane; then lay glass, ethylene-vinyl acetate copolymer, main grid-free rectangular battery cell, copper welding wire composite film, POE, and pretreated backplane in order, seal the edges after laying, laminate at 140°C for 15 minutes, frame, wire, and package to prepare a photovoltaic module; the backplane is divided into side A and side B, side A is the side in contact with the outside, and side B is the side connected to various photovoltaic modules, and the paint is applied to side A when coating. Detection test:
[0027] Flame retardant performance test: The backboard prepared by the present invention is cut into samples with a size of 80 mm×10 mm×4 mm, and tested according to the standard GB / T 2406.2-2009.
[0028] Hardness test: The back plate prepared by the present invention was used as a sample, and the hardness of the composite friction material was tested using a Vickers microhardness tester. Each sample was measured 20 times and the average value was taken (the load was 500 gf). The results are shown in the following table:
[0029] Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. From the experimental data, it can be seen that the various properties of the samples have no obvious fluctuations.
[0030] Comparative Example 1: The preparation step of the SiC enhanced flame retardant material is removed, and the rest is the same as Example 1. It can be seen from the experimental data that, compared with Example 1, the limiting oxygen index is reduced to 29.1%, and the hardness is reduced to 43. The reasons are analyzed as follows: by adding silicon carbide whiskers to the SiC enhanced flame retardant material, the strength and hardness of the material can be significantly improved, thereby enhancing the hardness of the sample of the present invention. Therefore, after the preparation step of the SiC enhanced flame retardant material is removed, the hardness is reduced; in addition, since the SiC enhanced flame retardant material also contains a certain amount of flame retardant element N, which can improve the flame retardant properties of the material, the flame retardant properties of the sample will also be reduced after it is removed, and the oxygen index is reduced.
[0031] Comparative Example 2: The preparation steps of the melamine-modified flame-retardant material and the polyphosphoric acid flame-retardant material are removed, and the rest are the same as Example 1. It can be seen from the experimental data that, compared with Example 1, the limiting oxygen index is reduced to 25.3%. The reason is analyzed as follows: the melamine-modified flame-retardant material and the polyphosphoric acid flame-retardant material prepared by the present invention contain a large amount of flame-retardant elements, which can significantly improve the flame retardant properties of the sample. Therefore, after removing them, the flame retardant properties of the sample are reduced, and the oxygen index is reduced.
[0032] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0033] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-efficiency battery assembly, characterized in that: The following steps are involved: Step 1: Mix melamine modified flame retardant material, SiC reinforced flame retardant material, polyphosphoric acid flame retardant material and 1,4-dioxane, then slowly add ethylenediamine and pyridine, reflux at 90-100°C for 3-5h, filter, wash with water, wash with alcohol, and dry after the reaction to obtain a composite flame retardant material; mix silicone resin, silica filler, composite flame retardant material, dispersant, and coupling agent, stir and ball mill thoroughly to obtain a coating; Step 2: Clean the backplane with ethanol, rinse with deionized water, apply paint, and cure at 100-180℃ for 1-2h to obtain a pretreated backplane; then lay glass, ethylene-vinyl acetate copolymer, main grid-free rectangular battery cell, copper welding wire composite film, POE, and pretreated backplane in sequence, seal the edges after laying, and then laminate, frame, wire, and package to prepare a photovoltaic module.
2. The method for preparing a high-efficiency battery assembly according to claim 1, characterized in that: In step 1, the preparation process of the melamine modified flame retardant material is as follows: melamine and deionized water are mixed, the oil bath is heated to 100-110° C., phytic acid and γ-aminopropyltriethoxysilane are added dropwise, and the reaction is continued for 5-7 hours to obtain a modified flame retardant liquid; The modified flame retardant liquid, cyanuric chloride and acid-binding agent triethylamine are mixed, and stirred at 15-20° C. for 4-5 hours to obtain a melamine-modified flame retardant material.
3. The method for preparing a high-efficiency battery assembly according to claim 2, characterized in that: The reaction molar ratio of phytic acid, melamine and γ-aminopropyltriethoxysilane is 1:(4-5):1; the reaction mass ratio of modified flame retardant liquid, cyanuric chloride and acid binding agent triethylamine is (3-4):2:
1.
4. The method for preparing a high-efficiency battery assembly according to claim 1, characterized in that: In step 1, the preparation process of the SiC reinforced flame retardant material is as follows: deionized water, anhydrous ethanol and γ-aminopropyltriethoxysilane are mixed, ultrasonically dispersed for 15-20 minutes, and then SiC whiskers are added, stirred and reacted at 45-50° C. for 30-40 minutes to obtain a modified SiC solution; The modified SiC solution, cyanuric chloride and acid-binding agent triethylamine are mixed, and stirred at 15-20° C. for 4-5 hours to obtain a SiC reinforced flame retardant material.
5. The method for preparing a high-efficiency battery assembly according to claim 4, characterized in that: The contents of the components of the SiC reinforced flame retardant material are as follows: by mass: 100-120 parts of deionized water, 200-220 parts of anhydrous ethanol, 2-3 parts of gamma-aminopropyltriethoxysilane, 2-3 parts of SiC whiskers, 1.8-2.0 parts of cyanuric chloride, and 1-2 parts of acid-binding agent triethylamine.
6. The method for preparing a high-efficiency battery assembly according to claim 1, characterized in that: In step 1, the preparation process of the polyphosphoric acid flame retardant material is: hexachlorotriphosphazene, 4-hydroxyphenyl phosphate and acetonitrile are mixed, stirred at 75-80° C. for 3-5 hours, and then pyridine is added to continue the reaction for 6-8 hours to obtain the polyphosphoric acid flame retardant material.
7. The method for preparing a high-efficiency battery assembly according to claim 6, characterized in that: The contents of the components of the polyphosphoric acid flame retardant material are as follows: by mass: 17-20 parts of hexachlorotripolyphosphazene, 34-40 parts of 4-hydroxyphenyl phosphate, 200-250 parts of acetonitrile, and 16-20 parts of pyridine.
8. The method for preparing a high-efficiency battery assembly according to claim 1, characterized in that: In step one, the contents of each component of the composite flame retardant material are: by mass, 180-200 parts of melamine modified flame retardant material, 310-320 parts of SiC reinforced flame retardant material, 270-280 parts of polyphosphoric acid flame retardant material, 150-350 parts of 1,4-dioxane, 4.8-5.2 parts of ethylenediamine, and 9.8-10.2 parts of pyridine.
9. The method for preparing a high-efficiency battery assembly according to claim 1, characterized in that: In step 1, the contents of the components of the coating are: by mass fraction, 15-20% silica filler, 10-15% composite flame retardant material, 0.5-1.5% dispersant, 0.5-1.5% coupling agent, and the remainder is silicone resin; the dispersant is oleamide; and the coupling agent is diethyl titanate.
10. The method for preparing a high-efficiency battery assembly according to claim 1, characterized in that: In step 2, the backplane is divided into side A and side B, side A is the side in contact with the outside, and side B is the side connected to various photovoltaic modules. When coating, the coating is applied to side A; lamination process parameters: lamination temperature is 130-140°C, and lamination time is 10-14min.